2023
DOI: 10.1186/s40066-023-00410-y
|View full text |Cite
|
Sign up to set email alerts
|

Road accessibility and agricultural extension services in Malawi

Abstract: Background In recognition of the potential importance of road access in the provision of and request for agricultural extension services, this study investigates whether and to what extent access to paved roads would influence farmers’ access to extension services, using a nationally representative sample of households and communities in Malawi. Our study proposes an extension access measure that reflects the diversity of agricultural topics and extension service providers available in the vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This finding also corroborates the findings of Lee et al (2023) that women farmers were predicted to have considerably lower extension access scores than men.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding also corroborates the findings of Lee et al (2023) that women farmers were predicted to have considerably lower extension access scores than men.…”
Section: Resultssupporting
confidence: 90%
“…This result confirms the findings of Daniel and Mulugeta (2017) that a one-minute increase in the distance of farmland from a farmer's home decreases the adoption of introduced soil conservation practices. Lee et al (2023) supported that road access strongly influences access to extension services. Similarly, Getu Mitiku and Tesfaye Lemma (2018) found that Distance to the nearest input market has a negative and significant influence on the probability of participation in agricultural extension services.…”
Section: Resultsmentioning
confidence: 88%
“…This result con rms the ndings of Daniel and Mulugeta (2017) that a one-minute increase in the distance of farmland from a farmer's home decreases the adoption of introduced soil conservation practices. Lee et al (2023) supported that road access strongly in uences access to extension services. Similarly, Getu…”
Section: Distance From Tomentioning
confidence: 89%